استخدام استراتیجیة المودیلات التعلیمیة وفق تمرینات المقتربات الخططیة وتاثیرھا في تعلم بعض المھارات الھجومیة المركبة بكرة السلة - عماد طعمة راضي (الرياضة المعاصرة, 2017)
The research includes four doors where the first section included the definition of research and introduction and the importance of research and the problem of research and included on the goals are - the use of educational models according to the exercises in the approach to learn in some of the offensive skills compound basketball. -Learning about the effect of educational models according to the exercises in the approach of the schematic in learning some of the offensive skills compound basketball. The research hypotheses. There are statistically significant differences between the results of the tribal tests and the results of the experimental tests of the experimental group and the control group in learning some of the basketball offensive skills. There are statistically significant differences between the results of the experimental tests of the experimental group and the control group in learning some of the basketball offensive skills. The second section includes the methodology used in the experimental and sample method. They are the students of the first stage, the College of Physical Education and Sport Science (50), as well as the tests used, the exploratory experiment, the tribal tests, the application of the educational models and the remote tests The third section included presentation, analysis and discussion of the results of the tribal and remote tests of the two groups The fourth section included the most important results, including - -The results showed that the use of the strategy of educational models is effective in learning some of the offensive skills compound basketball. The results showed that the special exercises have been effective in improving the learning of the members of the research sample in learning some offensive skills compound basketball